Dynamic model for polyethylene production in a multizone circulating reactor - Ghasem, N.M.; Ang, W.L.; Hussain, Mohd Azlan (Chemical Product and Process Modeling, 2008)
The multizone circulating reactor (MZCR) technology is a newly announced reactor design for solid-catalyzed gas-phase polymerization. The process is characterized by two hydrodynamically distinct but interconnecting polymerization zones, thus forming a continuous loop of polymer flow between the said zones. In the present study, a dynamic model for the MZCR reactor is developed to illustrate the basic dynamic behavior of the new reactor design; the model is used to study the copolymerization of ethylene with butene. Several parameter sensitivity analyses are performed to show the computer-simulated time responses for reactor temperature, number-average molecular weight, weight-average molecular weight, catalyst feed rate and the monomer concentration along the reactor length.